Listening Skills Integration through the Interdisciplinary Approach in Elementary Schools: Teaching Techniques and Practical Recommendations - Vonny Suhardiningsih; Herlina Usman; Ika Lestari (LPPM STKIP Kusuma Negara, 2026)
This research employed a systematic literature review (SLR) of seven international peer-reviewed journal articles published between 2020 and 2025. The literature search was conducted using the Scopus database keywords “listening skills” AND “elementary school” with inclusion criteria focusing on studies addressing listening skills, interdisciplinary learning, and elementary school contexts. Data were analyzed using thematic synthesis to identify instructional strategies, learning outcomes, and pedagogical implications. The findings indicate that listening skills play a fundamental role in language acquisition and require explicit instructional support and structured learning experiences to develop effectively. An interdisciplinary approach enhances listening skills by enabling students to learn language contextually through connections with other subjects such as science, art, and health. Instructional strategies including project-based learning, games, and gamification positively contribute to students’ motivation, collaboration, and critical thinking.The novelty of this study lies in synthesizing evidence on interdisciplinary listening instruction specifically in elementary education. Practically, the findings provide evidence-based guidance for teachers to design meaningful and participatory listening activities aligned with curriculum demands. This study highlights the relevance of integrating listening skills and elementary school contexts to improve language learning quality in the digital era.